Features of the psychosexual development of children born to women who received hormonal treatment during pregnancy - I V Kuznetsova; A N Grigoryan; N A Geppe; A A Koval-Zaytsev (IP Berlin A.V., 2015)
Hormone therapy is widely used in obstetric practice for the treatment of miscarriage, but, despite the known facts about the decisive influence of hormones on the sexual differentiation of the brain, long-term effects of intrauterine exposure to steroid drugs (drugs) on the formation of sexual behavior insufficiently studied. Therefore, the purpose of the study was to assess the performance of psychosexual development of children whose mothers received hormonal drugs during pregnancy. The cross-sectional study included 148 children whose mothers took estrogens and/or progestogens, and/or glucocorticoids, or did not take steroids (control group). The evaluation of indicators of mental development of children using the methods of «Age and gender identification», «Figure-posture-clothing», «Picture yourself», «Drawing the human behind the front» has been held.Results. Most of the children's sexual development was in line with the norm, gender and age identification formed by age and without features, elements of sexual dysontogenesis observed in isolated cases. Deviations were more common in girls whose mothers took estrogens and progestogens, and boys whose mothers received corticosteroids, but the proportion of these children were not significantly different from the proportion of children in the group of women who did not receive hormone therapy.Conclusion. The data obtained refute assumptions about the relationship of hormonal drugs during pregnancy with the development of disorders of puberty and sexual behavior anomalies in the offspring.